Understanding of Nanofiber Face Mask as Corona Virus Disease Prevention in Human - Tofan Agung Eka Prasetya; Indiah Ratna Dewi; Muhamad Rifki Taufik; Khandaker Fadwana Islam (Knowledge Dynamics, 2024)
Background: Corona virus has become a global issue. It makes various countries have taken this outbreak very seriously. One of the necessary precautions is by using a face mask. The nanofiber technology on face masks greatly helps the public and government to increase the prevention of disease spread. The purpose of this study was to conduct a systematic literature review on nanofiber face masks as human corona virus disease prevention. Methods: Stages of systematic literature review of 632 documents was carried out using text mining techniques, while hierarchical cluster analysis were carried out for the extraction of terms in documents. Results: The terms